PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN DESA STUDI DI DESA GIRI PURNO KECAMATAN RIMBO ILIR KABUPATEN TEBO - Miranti Miranti; Putut Haryanto (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
This research was conducted in Giri Purno Village, Rimbo Ilir District, Tebo Regency. The location of the research will be carried out in Giri Purno Village, Rimbo Ilir District, Tebo Regency. This location was chosen